2014
DOI: 10.2217/bmm.13.118
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-Mir-499 rs3746444 Gene Polymorphism is Associated with Susceptibility to Breast Cancer in an Iranian Population

Abstract: Our findings demonstrated that the hsa-mir-499 rs3746444 polymorphism is associated with higher risk of developing breast cancer in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 46 publications
1
52
0
Order By: Relevance
“…There were fifteen studies of caucasian descent and twenty-four studies of Asian descent. The genotype distributions in the controls of fourteen studies were not conforming to HWE (p<0.05) (Okubo et al, 2010;Akkiz et al, 2011;Ling et al, 2011;Mittal et al, 2011;Zhou et al, 2011;Xiang et al, 2012;Shan et al, 2013;Vinci et al, 2013;Wei et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Ma et al, 2014;Omrani et al, 2014;Wang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were fifteen studies of caucasian descent and twenty-four studies of Asian descent. The genotype distributions in the controls of fourteen studies were not conforming to HWE (p<0.05) (Okubo et al, 2010;Akkiz et al, 2011;Ling et al, 2011;Mittal et al, 2011;Zhou et al, 2011;Xiang et al, 2012;Shan et al, 2013;Vinci et al, 2013;Wei et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Ma et al, 2014;Omrani et al, 2014;Wang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…One study was excluded as it was not associated with hsa-mir-499 rs3746444 A>G (Kupcinskas et al, 2012). After further excluding two abstracts (Hu et al, 2009;Hwang et al, 2010), thirty-nine case-control studies involving 14,136 cases and 16,937 controls were selected for meta-analysis (Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Liu et al, 2010;Okubo et al, 2010;Srivastava et al, 2010;Akkiz et al, 2011;George et al, 2011;Ling et al, 2011;Mittal et al, 2011;Vinci et al, 2011;Zhou et al, 2011;Alshatwi et al, 2012;Chu et al, 2012;Kim et al, 2012;Min et al, 2012;Xiang et al, 2012;Zhou et al, 2012;Ahn et al, 2013;Lv et al, 2013;Shan et al, 2013;Song et al, 2013;Umar et al, 2013;Vinci et al, 2013;Wei et al, 2013;Wu et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Chu et al, 2014;Du et al, 2014;Gutierrez-Camino et al, 2014;Hasani et al, 2014;Hou et al, 2014;Hu et al, 2014;Ma et al, 2014;Omrani et al, 2014;Pu et ...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative evidence suggests that the dysregulation of miRNA expression is involved in the tumorigenesis by acting as tumor suppressors or oncogenes (11-15). Single-nucleotide polymorphisms (SNPs) or mutations in miRNA genes can affect the miRNA biosynthesis and expression of target genes, therefore resulting in diverse functional consequences and thereby possibly representing potentially important biomarkers for the prognosis of cancer (7,(16)(17)(18).The pri-miR-34b/c gene resides in a CpG island within the intron of the B-cell translocation gene 4. Therefore, it is expected that pri-miR-34b/c is co-transcribed by either the promoter of the protein-coding gene or by its own transcription initiation region, as is the case with the majority of miRNAs, whether they are intergenic or located within the introns of protein coding genes (9).…”
mentioning
confidence: 99%
“…Therefore, a function SNP in miRNA genes may affect many signaling pathways by altering the expression levels of thousands of genes (Wu et al 2014). Previous studies have shown that SNPs in miRNA genes are associated with the susceptibility to many disease, including cancer (Omrani et al 2014). Previous studies revealed that miR-146a rs2910164 (Xiong et al 2014), miR-149 rs71428439 , miR-196a2 rs11614913 (Zhou et al 2010;Zhi et al 2012), and miR-499 rs3746444 (Zhi et al 2012;Liu et al 2014) were related to the risk of cardiovascular diseases, including coronary artery disease (CAD), ischemic stroke and MI.…”
Section: Introductionmentioning
confidence: 99%